Integrating State Sovereignty and International Obligations: A Comparison of Indonesian and Philippine International Law into Domestic Constitutional Systems - Ni Ketut Sari Adnyani; Kadek Dedy Suryana; Ni Made Wiratini; Komang Putri Komang Febrinayanti Dantes; Princess Alyssa D. Tee-Anastacio (Faculty of Law Universitas Lampung, 2025)
Indonesia and the Philippines integrate international law into their constitutional systems to uphold global commitments, protect human rights, and strengthen the rule of law. This study examines how both countries regulate state sovereignty and position international obligations within the national legal order by addressing two questions: how sovereignty is constructed in the Indonesian and Philippine constitutions and how each state views the relationship between sovereignty and international obligations; and how international law, including treaties and customary rules, is integrated into their domestic legal systems. Using a normative-comparative approach, the study analyzes similarities and differences in the acceptance, ratification, and implementation of international norms at the national level. The findings indicate that although both countries uphold state sovereignty, they differ in how international law is adopted and given binding force. These differences demonstrate how constitutional structures and political-legal orientations influence the implementation of international obligations and shape the relationship between national and international law.